(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
It differs in the fact that when teaching preschool children to draw, the program is complicated in stages. The first lesson of drawing begins with the introduction of paper and pencils. Understand that these materials differ from toys to different subjects known to childrentiradi pedagogical children. With pencils can perform various types of activities. The paper was clean, traces appeared on it from the movement of the pen. The opened tip of the pen leaves a mark on the paper. And the two ends do not leave a trace. If you press slowly, then on paper there are no traces of it. If pressed hard, the paper can be torn off. Showing such an explanation and actions will arouse interest in drawing in children. In addition to these, it included a program to train simple technical skills such as knowing how to properly hold a pencil, a mustache, how to use them in order, how to draw a paint on the tip of a mustache.